Persepsi dan Tingkat Keselamatan Pengguna Sepeda di Kota Palu - Ridwan, N.A.; Ramlan, R.; Lestari, S.P.; Fadilah, I. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
Since the outbreak of the Covid-19 Pandemic in Indonesia, there has been an increase in public interest in using bicycles, especially when exercising. This study aims to determine the characteristics, behavior, safety, habits, and perceptions of bicycle users in Palu City at this time, then a questionnaire was distributed with a total of 132 participating respondents. The method of descriptive and Frekuensi data analysis shows that the characteristics of cyclists generally cycle in weekend (88,6%) which is to exercise or visit sightseeing spots (78%), cyclist behavior is generally still good in the relationship between road users (98,5%), cyclist safety is indicated by the accident rate of 43,2% which is generally a single traffic accident (91,2%), cyclist generally increases their habit of exercising or visiting the sightseeing spots (10,6%) and visiting friends or family’s houses (5,3%) and the perception of cyclist who generally understands safety requirements when cycling (79,5%) and agrees that cycling can improve environmental quality (90,2%).